Inter-Firm Executive Mobility and Corporate Social Responsibility: Evidence From China - Wang, Jun; Cao, Jieling (Frontiers in Psychology, 2022)
The executives of listed firms play an important role in the fulfillment of corporate social responsibility (CSR). Based on behavioral consistency theory, this study examines the association of CSR performance among multiple firms for the same executive served at different times. By tracking the movement of executives across Chinese listed firms over the period 2010-2019, we find that there is a significantly positive association between the predecessor and the successor firm’s CSR performance for the same executive, implying that individual’s value and preference for CSR maintain consistency within a certain period of time. We also find that a longer employment gap and lower internal control effectiveness will damage the association of CSR performance between the predecessor and the successor firm. Our results are robust to testing in subsamples and controlling the endogeneity problems. Our conclusion provides a new perspective to understand the influence mechanism of CSR performance in the context of inter-firm executive mobility and provides empirical evidence for listed firms to improve their decision-making in hiring and evaluating executives.